PENGARUH PRAPERLAKUAN BAHAN BAKU TERHADAP KUALITAS PAPAN LAMINA ROTAN - Adi Santoso; Gustan Pari; Krisdianto; Karnita Yuniarti; Jasni; Heru Wibisono (Jurnal Penelitian Hasil Hutan, 2022)
Rattan has the potential to be developed into composite products with gluing technology into laminated rattan. However, as araw material, rattan has a weakness, namely that it contains chemical components that inhibit the adhesive bond with the chemicalmolecules of rattan. In an effort to overcome this, a technique for making composite rattan was carried out in order to obtain dataon the effect of pretreatment on rattan as a raw material. Rattan as a raw material is first dried by microwave, hydrothermalevaporation and conventional methods in order to reduce the levels of adhesive chemical components contained in rattan. This paperpresents the results of research on the technology of making laminated rattan from the Batang (Calamus zolingerii) large diameter(>20 mm) with mangium tannin adhesive. The results showed that the pre-treatment of rattan as a raw material in the form ofdrying by means of oven, steam, frying, hydrothermal, and microwave, each produced a different effect on the chemical componentscontained and the degree of crystallinity. The best rattan laminate board was obtained from rattan which was pretreated using a 1kW microwave oven (input) with a maximum energy strength of 50%.